P121 An audit of ambulatory oxygen assessments utilising a pre-established blinded treadmill protocol. (11th November 2022) - McArthur, S; Baxter, S
Abstract : Introduction: A blinded ambulatory oxygen assessment protocol on a treadmill was established in 2005. Patients perform 2 walking tests, up to fifteen minutes each, on a treadmill at a set speed with a 30 minute rest between tests. The patient wears nasal cannulae on both tests, through which they receive 2L/min of air or Oxygen. Patients rate their breathlessness on a BORG scale every minute and this is recorded with Oxygen saturation via ear probe and heart rate. An increase in distance (10%) or decrease in BORG scores (1 point/10%) would indicate a need for ambulatory Oxygen prescription. The British Thoracic Society (BTS) 2015 ambulatory Oxygen therapy assessment protocol also states that an increase in SpO2 to ≥90% throughout the test would show a benefit to the patient 1 . Aim: How many patients referred for assessment would benefit from prescription of ambulatory Oxygen based on the current BTS protocol? Methods: Test results, demographic and clinical data were collated for all patients referred for ambulatory Oxygen assessment over 1 year. Results: 88 patients were referred for assessment with 18 excluded (n=70). 11 patients only carried out the baseline test on air without progressing to the second test on oxygen as there was no significant desaturation during exercise. Of the 59 remaining patients 34 would be recommended ambulatory oxygen therapy, 19 would not and the remaining 6 may require higher flow rates than the 4L/min O2 that is the highest rate within the protocol. Only 18 patients (18/59=31%) had a decrease in BORG (felt better) by 10% or 1 point whilst on supplemental O2. 10 patients (10/59=17%) reported higher BORG scores on Oxygen (?fatigue, ? walked further). Conclusion: Of the 70 patients included in the audit 34 (48.57%) would be recommended ambulatory oxygen therapy, 30 (42.86%) would not and the remaining 6 (8.57%) may require higher flow rates than the 4L/min that is the highest rate within the protocol. This protocol has been particularly useful during the COVID pandemic and the SOP has been shared with other departments. References: Hardinge M, Annandale J, Bourne S, et al . British Thoracic Society guidelines for home oxygen use in adults: accredited by NICE. Thorax 2015;70 :i1-i43.